Sustainable Tourism Management Strategy at Punaga Beach: A SWOT and AHP Approach for Environmental, Socio-Economic, and Cultural Sustainability - Ina Nurfitri; Sugeng Utaya; Dwiyono Hari Utomo (JAMBURA GEO EDUCATION JOURNAL, 2025)
Tourism has developed into an important economic sector with great potential for growth. However, the sustainability of the industry remains a challenge due to issues such as resource exploitation, ecological degradation, and lack of local community involvement. In light of these challenges, sustainable tourism has become a central theme in tourism destination management across Indonesia, including Punaga Beach in South Sulawesi. This study explored the characteristics of sustainable tourism management at Punaga Beach and the factors that influence its success. The study adopted a quantitative approach using the Analytical Hierarchy Process (AHP) and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Data were collected through interviews with relevant stakeholders, questionnaires, and field observations. The findings indicate that tourism management at Punaga Beach needs to be strengthened through strategies involving collaboration between the government, local communities, and the private sector. Based on the AHP analysis, the priority factors in sustainable tourism management include improving human resource quality, enhancing facilities, and raising community awareness of environmental conservation. This study provides recommendations for sustainability-based management improvements to achieve more efficient and long-term tourism development at Punaga Beach